2019
DOI: 10.31234/osf.io/frmnx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Issues, problems and potential solutions when simulating continuous, non-normal data in the social sciences

Abstract: Computer simulations have become one of the most prominent tools for methodologists in the social sciences to evaluate the properties of their statistical techniques and to offer best practice recommendations. Amongst the many uses of computer simulations, evaluating the robustness of methods to their assumptions, particularly univariate or multivariate normality, is crucial to ensure the appropriateness of data analysis. In order to accomplish this, quantitative researchers need to be able to generate data wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The small-scale simulation study shown in Section 3 highlights an important aspect of simulation research as it is conducted in the social sciences: there is a differential effect that the method of simulation has on simulation results. Although there is very little research on this, Astivia andZumbo (2015, 2018) and Falk (2018) have shown that the data-generating method can be considered as a simulation condition in itself. Their results support the fact that, even for the same marginal non-normality, different ways to generate the data can result in different conclusions for computer studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The small-scale simulation study shown in Section 3 highlights an important aspect of simulation research as it is conducted in the social sciences: there is a differential effect that the method of simulation has on simulation results. Although there is very little research on this, Astivia andZumbo (2015, 2018) and Falk (2018) have shown that the data-generating method can be considered as a simulation condition in itself. Their results support the fact that, even for the same marginal non-normality, different ways to generate the data can result in different conclusions for computer studies.…”
Section: Discussionmentioning
confidence: 99%
“…An important feature of X that allows it to become a true multivariate generalization is that univariate normal distributions are closed under convolutions, that is, linear combinations of normally distributed random variables result in another normally distributed random variable. If the random variables being correlated do not posses this property, the central limit theorem can take over and weaken the non‐normality aspects that researchers are interested in using as simulation conditions (Astivia, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation of correlated multivariate normal data, including specification of factor loadings, is simple. Simulation of non-normal correlated data, however, is fraught with issues (Astivia, 2020). The most common method for simulating continuous data is the power method of Fleishman (1978), extended in Vale and Maurelli (1983), Headrick and Sawilowsky (1999), and Headrick (2002).…”
Section: σ = ∆∆ + ψmentioning
confidence: 99%
“…The most common method for simulating continuous data is the power method of Fleishman (1978), extended in Vale and Maurelli (1983), Headrick and Sawilowsky (1999), and Headrick (2002). But as Astivia (2020) notes, there are a multiplicity of solutions with no clear guidance to determine which solution is correct. Other proposed methods include using transformations of univariate random variables in Mattson (1997), an iterative algorithm in Ruscio and Kaczetow (2008), vines in Grønneberg and Foldnes (2017), and piecewise linear transforms in Foldnes and Grønneberg (2022), and many others.…”
Section: σ = ∆∆ + ψmentioning
confidence: 99%